2005
DOI: 10.1159/000082090
|View full text |Cite
|
Sign up to set email alerts
|

Large Liver Cell Dysplasia in Hepatitis B Virus X Transgenic Mouse Liver and Human Chronic Hepatitis B Virus-Infected Liver

Abstract: Objectives: Large liver cell dysplasia (LCD) is frequently associated with hepatitis B virus (HBV), but it remains uncertain whether it is reactive, senescent or preneoplastic. Methods: The HBX transgenic mice and normal control mice were sacrificed at 1, 3, 5, 7, 9, 11, 13 and 15 months after birth. Twenty-three cases of human B viral chronic hepatitis/cirrhosis with prominent LCD were selected. The immunohistochemical stain of proliferating cell nuclear antigen (PCNA), transferase-mediated dUTP-biotin nick e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
2
25
0
1
Order By: Relevance
“…In the study of chronic B viral hepatitis/cirrhosis, most LCC showed a higher proliferation rate and lower rate of apoptosis than normal hepatocytes, and the difference in proliferation and apoptosis rate, measured in individual cases using the same tissue block, showed a gradual increase in cellular net gain from the hepatocyte without LCC, to those with LCC, to overtly malignant hepatocytes. This result might partly validate LCC as a slowly proliferative but not resting (quiescent) lesion [37]. In addition, the expression of the senescence-associated marker b-galactosidase was positive in only a fraction of large dysplastic hepatocytes [37].…”
Section: Proliferation and Apoptosis Markersmentioning
confidence: 86%
“…In the study of chronic B viral hepatitis/cirrhosis, most LCC showed a higher proliferation rate and lower rate of apoptosis than normal hepatocytes, and the difference in proliferation and apoptosis rate, measured in individual cases using the same tissue block, showed a gradual increase in cellular net gain from the hepatocyte without LCC, to those with LCC, to overtly malignant hepatocytes. This result might partly validate LCC as a slowly proliferative but not resting (quiescent) lesion [37]. In addition, the expression of the senescence-associated marker b-galactosidase was positive in only a fraction of large dysplastic hepatocytes [37].…”
Section: Proliferation and Apoptosis Markersmentioning
confidence: 86%
“…Koo et al [26] demonstrated that hepatocytes with LCC showed a significantly higher proliferating cell nuclear antigen (PCNA) LI in HBV X transgenic mice than did normal hepatocytes of control mice and had a higher PCNA-LI than hepatocytes without LCC, although not significantly, in human CVH-B sections using immunohistochemistry. PCNA protein, a cofactor of DNA polymerase δ, plays an important part in DNA replication in response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the DNA methylation changes leading to cancer, we created DNA methylation maps for liver tissues from HBx TG mice and their wild-type littermates at early (3-mo-old) and late (13-mo-old) stages of tumor development (6,19). We sequenced the methylated DNA from at least two independent preparations for each sample using the methylated CpG island recovery assay (MIRA) (20).…”
Section: Global Comparison Of Dna Methylation In Normal and Hbx Tg Mousementioning
confidence: 99%